RESULTS OF ARCHAEOLOGICAL FIELDWORK IN THE DISTRICTS OF DAK SONG AND DAK MIL, DAK NONG PROVINCE, IN 2018 - Thanh Vuong Nguyen; Tien Duc Vu; Xuan Hung Le (Tạp chí Khoa học Đại học Đà Lạt, 2024)
This study investigates the archaeological potential of Dak Nong Province, Vietnam, as revealed by fieldwork in the Dak Song and Dak Mil districts. We conducted field surveys at various sites, resulting in the discovery of a rich prehistoric heritage in the region, despite challenges posed by complex natural conditions. While artifact distribution and concentration vary across sites, we identified significant concentrations in areas near lakes, rivers, and streams. We find that at locations such as Village 9A, volcanic Lake Dak Mil, and Tay Son Village, traces of concentration are faint. In contrast, at sites such as Dak Peur Border Gate and Tan Lap Village, there are traces of a dense population and long occupation by prehistoric people. The prehistoric inhabitants of Dak Mil and Dak Song districts often lived along lakes, rivers, and streams that did not dry up in the dry season; they lived in a large area and were highly mobile. Our preliminary research highlights the value of Dak Nong Province in studying the early stages of prehistory and cultural development in the Central Highlands region of Vietnam. This also underscores the importance of preserving and promoting archaeological heritage in Dak Mil and Dak Song districts.